Analisis Efisiensi Pemasaran Kopi Robusta - Dian Safitri; Siswanto Imam Santoso; Suryani Nurfadillah (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Pati, 2025)
ENGLISH Robusta coffee is a leading commodity in Keling Subdistrict, Jepara Regency. However, farmers' bargaining position in the robusta coffee market is weak due to limited capital and lack of access to market information. This study aimed to analyze the marketing channel patterns, marketing functions, and marketing efficiency of robusta coffee in Keling Subdistrict. The research was conducted in Tempur Village and Damarwulan Village from January to February 2023 using a survey method. The total of 100 farmer respondents were selected through simple random sampling, while marketing institution respondents were determined using the snowball sampling. Data analysis methods included descriptive analysis for examining marketing channels and marketing functions. Quantitative analysis was used for evaluating marketing costs and margins, farmer's share, and Marketing Efficiency (EP). The results identified six robusta coffee marketing channel patterns in Keling Subdistrict. The marketing functions performed by the marketing institutions include exchange functions, physical functions, and facilitating functions. The most efficient marketing channel based on margins (IDR 709) was Channel 4 (farmer – coffee processor). Meanwhile, the most efficient marketing channel based on the farmer's share (97.50%) and Marketing Efficiency (EP) (2.56%) was Channel 6 (farmer – factory). INDONESIA Kopi Robusta merupakan komoditas unggulan di Kecamatan Keling Kabupaten Jepara. Posisi tawar petani dalam pemasaran kopi robusta lemah karena kurangnya modal dan akses informasi pasar. Penelitian bertujuan menganalisis pola saluran pemasaran, fungsi-fungsi pemasaran, dan efisiensi pemasaran kopi robusta di Kecamatan Keling. Penelitian dilaksanakan di Desa Tempur dan Desa Damarwulan pada bulan Januari sampai Februari 2023 menggunakan metode survei. Metode pengambilan responden petani menggunakan simple random sampling sebanyak 100 responden. Pengambilan sampel lembaga pemasaran menggunakan snowball sampling didapatkan sebanyak 7 responden. Metode analisis data secara deskriptif untuk analisis pola saluran pemasaran dan fungsi-fungsi pemasaran. Data dianalisis secara kuantitatif untuk analisis biaya dan margin pemasaran, analisis farmer’s share, dan analisis Efisiensi Pemasaran (EP). Hasil penelitian didapatkan 6 pola saluran pemasaran kopi robusta di Kecamatan Keling. Fungsi pemasaran yang dilaksanakan oleh lembaga pemasaran adalah fungsi pertukaran, fungsi fisik, dan fungsi fasilitas. Saluran pemasaran yang paling efisien berdasarkan nilai margin pemasaran (Rp 709) adalah saluran 4 (petani – pengrajin kopi). Saluran yang paling efisien berdasarkan nilai farmer’s share (97,50%) dan Efisiensi Pemasaran (EP) (2,56%) adalah saluran 6 (petani – pabrik).